Challenges and Opportunities for Strengthening Bottom‐Tow Fisheries Sustainability - Suresh A. Sethi; Robert D. Murphy; Matthew R. Baker; Anita C. Kroska; Haraldur A. Einarsson; Owen S. Hamel; Shelton J. Harley; Pingguo He; James Ianelli; Stan Kotwicki; Robert A. McConnaughey; Chris McGonigle; et al. (Fish and Fisheries, 2026)
Bottom‐tow gear fisheries (trawls and dredges) produce ~24 million mt of harvest annually, representing a globally important animal‐sourced food system. While many are currently sustainably managed, growing concern over the potential for ecosystem impacts from bottom‐tow gears has increased pressure to improve these fisheries. We assembled an international working group of > 30 contributors, including fishing industry participants, managers, non‐governmental ocean conservation organization representatives, and scientists to synthesize obstacles to bottom‐tow fisheries sustainability and to develop expert‐based recommendations to operationalize sustainability advancements moving forward. We identified 30 key gaps impeding bottom‐towed fisheries sustainability spanning 6 core challenge areas including: seafloor disturbance, bycatch and discards, management design and implementation, fishing operations, cross‐sector conflicts, and public perception and communication. We generated 28 priority recommendations to address bottom‐tow fisheries sustainability obstacles with themes including: addressing data gaps, advancing mechanistic understanding and modelling tools, strengthening management processes, and improving knowledge sharing and communication. Cross‐disciplinary and diverse system experience among fisheries and marine ecosystem stakeholders will be critical for operationalizing bottom‐tow fisheries sustainability advancements. As the global human population approaches 10 bn in the next 30 years, ensuring sustainable wild capture fisheries is an imperative for feeding the world. Outputs from this synthesis serve as a resource for fishing and marine ecosystem stakeholders to identify key challenge areas and associated entry points for solutions‐oriented efforts to improve the sustainability of bottom‐tow fisheries.

Machine learning derived abdominal aortic calcification is associated with physical frailty in community-dwelling adults: the UK Biobank Imaging Study - Abadi K. Gebre; Marion Mundt; Elsa Dent; James Webster; Afsah Saleem; Syed Zulqarnain Gilani; Yuandan Zhang; Cassandra Smith; Parminder Raina; John P. Kemp; William D. Leslie; John T. Schousboe; et al. (GeroScience, 2026)

Signatures of Radiation‐Induced Stress and Putative Selection on Immune Targets in Chornobyl Wolves - Cara N. Love; Stacey L. Lance; Thomas G. Hinton; Nicolas Rochette; James C. Beasley; Dmitry Shamovich; Michael E. Byrne; Brian Nadel; Sarah C. Webster; Shane C. Campbell‐Staton (Molecular Ecology, 2026)
Investigating the physiological and evolutionary consequences of contaminant exposure in wild populations is critical for understanding long‐term ecological impacts of anthropogenic change. However, how and why species persist, even thrive, in highly contaminated regions in the absence of humans remains a topic of much debate. We examined the regulatory and genomic impacts of multigenerational chronic radiation exposure to grey wolves ( Canis lupus ) within the Chornobyl Exclusion Zone. Wolves within the exclusion zone are at an estimated seven times greater density than surrounding preserves, despite lack of physical barriers to dispersal and chronic exposure to elevated radiation dose. Demographic analyses of genetic variation and home range modelling further suggest that ecological factors may support the wolf population within the exclusion zone. Wolves within Chornobyl exhibit altered leukocyte composition and regulatory signatures within the blood transcriptome that support significant alterations to metabolic and immune response pathways, particularly those influential in DNA damage response indicating radiation‐induced immune modulation. Selection scans across genes within the blood transcriptome revealed multiple regions of accelerated Chornobyl‐specific divergence at loci with known roles in immunity and response to oncogenesis. Together, these data provide evidence that chronic exposure to ionising radiation may be a significant source of ongoing natural selection in an apex predator after a single contamination event, highlighting multigenerational impacts beyond initial exposure. Further, these results highlight the potential contributions of natural selection to species persistence and proliferation in highly contaminated ecosystems.

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

A comparison of dating models for reservoir sediment records using mass accumulation, radioisotopes, and Bayesian statistics - Benjamin C. Webster; Joseph M. Smoak; Richard S. Vachula; Matthew N. Waters; Stephen W. Golladay (Journal of Paleolimnology, 2026)
Paleolimnological investigations of reservoirs (i.e. human-made lakes) are becoming more common, establishing a need to explore dating approaches for sediment records from reservoirs. Traditional dating methodologies such as Constant Rate of Supply (CRS), 137 Cs, and Mass Accumulation Rate (MAR) have been utilized for sediment records from reservoirs for decades. However, with the advent of newer Bayesian approaches, such as the Bacon and Plum models, ambiguity persists for researchers when selecting a particular dating model. This study aims to quantify and compare the output differences among various dating models for the same sediment records and provide a discission-making framework based on practical constrains, rather than to validate which model is most accurate. Here we investigated the differences among age model outputs (dates and sedimentation rates) generated with CRS, MAR, Plum, and Bacon for three reservoirs in the Southeastern United States. Though they are all viable age models, their utility varies with research question, application, and financial cost. MAR and Bacon produced similar linear age models. The sedimentation rate for MAR was a static value throughout the record, while Bacon’s had more variable and significantly larger sedimentation rate than MAR for each reservoir studied. Both MAR and Bacon are more practical when there is a limited budget or less time for analysis. CRS and Plum produced similar non-linear age models, with CRS and Plum having the smallest and second smallest region of error, respectively. Similarly, CRS and Plum sedimentation rates exhibited aligned variations of sedimentation rates for two of the three sediment records analyzed. CRS and Plum dates and sedimentation rates were more similar when sediment records had a larger excess 210 Pb total inventory. We found the smallest differences among model outputs, < 5% difference based on a RMSE normalized ‘record age ratio’, when models utilized the same input data (i.e. top–bottom dates for MAR with Bacon and radioisotope for CRS with Plum). Generally, CRS and Plum would be preferred when there is ample time and funds for the lengthy radioisotope analysis and its higher costs. If there are additional known dates to incorporate into a model, we encourage the use of Plum.

Correction to: The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2026)

Soil ingestion: An important contamination pathway for toxic element exposure in wild herbivores - Andrea B. Webster; Nigel C. Bennett; Marcus Clauss; Andre Ganswindt; Andrew J. Abraham (Science of The Total Environment, 2026)

Diverging effects of global change on future invasion risks of Agama picticauda between invaded regions: Same problem, different solutions - Nicolas Dubos; Steven Calesse; Kathleen C. Webster; Chloé Bernet; Gregory Deso; Thomas W. Fieldsend; Saoudati Maoulida; Soulé Mounir; Xavier Porcel; Jean-Michel Probst; Hindatou Saidou; Jérémie Souchet; et al. (Science of The Total Environment, 2025)

System-wide assessment of plastic pollution in Indonesia: external stakeholder mapping - Spyridoula Gerassimidou; Mike Webster; Andre Kuncoroyekti; David C. Wilson; Susan Jobling; Eddy Soedjono; Elena Lovat; Eleni Iacovidou (Environment Systems and Decisions, 2025)
Recent global initiatives, such as the Global Plastics Treaty, highlight the urgency for a systems-based approach to address the risks associated with plastic pollution. However, the implementation of such initiatives is often hindered by the absence of clear criteria for what constitutes a systemic approach and who is included within it. This study offers a comprehensive analysis of external stakeholders, those who are not directly engaged in the physical flow of plastics, contrasted with internal stakeholders, who play direct roles in the physical production, consumption and waste generation and management. While internal stakeholders have traditionally received increased attention in value chain studies, external stakeholders remain largely overlooked. To address this gap, this research introduces a novel approach, embedded in the systems-based method, called Complex Value Optimisation for Resource Recovery (CVORR), to identify, map and categorise external stakeholders in the plastics value chain in Banyuwangi, Indonesia, based on organisation type, activities, and interest. The study reveals a complex system of 111 external stakeholders consolidated into 11 groups that are engaged across various operational stages and spatial levels. By integrating stakeholder theory and analytical tools such as the Mendelow matrix, the study uncovers underlying power dynamics and significant lock-ins that arise where the emphasis on downstream waste management overshadows preventive upstream measures. The findings highlight the importance of fostering communication and collaboration among stakeholders and creating partnerships within and across stakeholder groups to drive systemic change. Engaging effectively throughout the plastics value chain can pave the way for tailored solutions to local challenges, thereby enhancing sustainability and facilitating alignment with the Sustainable Development Goals. Ultimately, this study advocates for coordinated efforts, ensuring that policy interventions and local actions support a comprehensive, circular approach to effective plastics management.

Optimal dose of green and blue spaces at home for improving kidney health: A population-weighted analysis - Yuwen Yang; William C. Sullivan; Lan Luo; Huan Lu; Lan Wang; Chris Webster; Bin Jiang (Urban Forestry & Urban Greening, 2025)

Mechanically robust non-isocyanate polyurethane coatings with scale-independent anti-icing performance - Nastaran Shahzadeh; Ivan Hevus; James Bahr; Dean C. Webster (Chemical Engineering Journal, 2025)

A review of dietary DNA metabarcoding in marine vertebrates: a new frontier in sea turtle foraging ecology? - Sophia A. Coveney; Tamsyn M. Uren Webster; Sofia Consuegra; Graeme C. Hays; Nicole Esteban (Marine Biology, 2025)
Diet characterisation is important for understanding trophic roles of animals across space and time, including in response to climate change. This has led to the development of a large range of dietary analysis techniques, from centuries-old morphological stomach analysis to recent molecular techniques. Given the difficulties and limitations of direct analysis in marine animals, here we review DNA-based methods of marine vertebrate diet analysis, examining the proliferation of studies over the last two decades. We identify a keystone taxon, sea turtles, where DNA-based approaches have had limited use, but offer great potential for characterising diet across species, life stages and regions. We show that contemporary molecular techniques can overcome some limitations of traditional methods based on morphological identification, such as the ability to identify rapidly digested food items. We report on the development of DNA metabarcoding protocols that enable simultaneous identification of many diet item sequences from heterogeneous samples. DNA metabarcoding can increase taxonomic resolution, improve the identification of certain items (e.g., gelatinous organisms), and increase the comprehensiveness of diet characterisation, particularly in combination with other techniques. However, careful methodological development and finer optimisation of metabarcoding protocols (e.g., appropriate primer selection, blocking of host DNA amplification) are necessary to improve results. Combination approaches to sea turtle dietary analysis and further experimentation with metabarcoding methodology will help to characterise variations and effectively monitor shifts in diet composition in response to environmental changes such as rising sea temperatures and displacement to alternative foraging grounds.

Effective treatment of energetic containing wastewater in a sequential anaerobic-aerobic membrane bioreactor (MBR) system - Part 1: Treatment of IMX-104 wastewater - Mark E. Fuller; Paul C. Hedman; Kung-Hui Chu; Todd S. Webster; Charles E. Schaefer; Danielle N. Tran; Paul B. Hatzinger (Chemosphere, 2025)

The attribution of human health outcomes to climate change: transdisciplinary practical guidance - K. L. Ebi; A. Haines; R. F. S. Andrade; C. Åström; M. L. Barreto; A. Bonell; K. Bowen; N. Brink; C. Caminade; C. J. Carlson; R. Carter; P. Chua; et al. (Climatic Change, 2025)

Quantification of methyl glyoxal in New Zealand Mānuka honey and honey meads - Claire E. Webster; David Barker; Rebecca C. Deed; Lisa I. Pilkington (Food Chemistry, 2025)

Correction to: N‑doped carbon nanospheres as selective fluorescent probes for mercury detection in contaminated aqueous media: chemistry, fluorescence probing, cell line patterning, and liver tissue interaction - Soheil Sojdeh; Ali Banitalebi Dehkordi; Alireza Badiei; Ali Zarrabi; Pooyan Makvandi; Milad Ashrafizadeh; Mohammad Reza Saeb; Eder C. Lima; Mohammad Rabiee; Mohsen Asadnia; Thomas J. Webster; Navid Rabiee (Environmental Science and Pollution Research, 2025)

Perfluorooctanoic acid increases serum cholesterol in a PPARα-dependent manner in female mice - G. Nielsen; D. D. Gondim; M. C. Cave; W. J. Heiger-Bernays; T. F. Webster; J. J. Schlezinger (Archives of Toxicology, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Evaluation of adhesion and fouling-release properties of non-toxic fouling-release coatings applied to oil boom materials - Jackson Benda; Madhura Pade; Ihor Tarnavchyk; Ryan Burgett; Jonas Sahouani; James Bahr; Kailey Richard; Kelli Z. Hunsucker; Geoffrey Swain; Shane Stafslien; Dean C. Webster (Biofouling, 2025)

Understanding the role of micro-organisms in the settlement of coral larvae through community ecology - Abigail C. Turnlund; Paul A. O’Brien; Laura Rix; Nicole Webster; Miguel Lurgi; Inka Vanwonterghem (Marine Biology, 2025)
Successful larval recruitment is essential to the growth of coral reefs and therefore plays a key role in the recovery of degraded reefs worldwide. The rising intensity and frequency of environmental disturbance events and their effect on the establishment of new corals is outpacing the natural capacity of coral reefs to recover. To counter this, restoration programmes are increasingly turning to interventionist approaches to enhance coral recruitment, including mass-breeding corals in aquaria for subsequent deployment in the field. Coral sexual propagation has the potential to generate large numbers of genetically diverse coral recruits, but widespread application is still limited by the ability to reliably guarantee the successful settlement of coral larvae. Identifying the origins of biochemical cues that enhance coral settlement is a prerequisite to improving coral larval settlement on key locations and substrates. Microbial biofilms and microbes associated with crustose coralline algae have been shown to induce coral larval settlement, yet the specific taxa and mechanisms involved are poorly understood. In this review we synthes current literature on microbial settlement cues and the challenges associated with untaizengling the origin of individual cues originating within complex microbial communities. Furthermore, we call attention to the importance of interrogating microbial interactions with a holistic community approach to further our knowledge of both coral larval settlement inducers and inhibitors. Obtaining a better understanding of microbial interactions associated with coral settlement will lead to more effective approaches to restoration, from engineering inductive microbial communities to synthesising biochemical cues that can support coral larval settlement for aquaculture and reef recovery.

Molecular analysis confirms Agama picticauda invasion on Western Indian Ocean islands - Markus A. Roesch; Kathleen C. Webster; Nicolas Huet; Oliver Hawlitschek; Youssouf Mohamed; Sohan Sauroy-Toucouère; Philipp Wagner; Andreas Schmitz (Biological Invasions, 2025)
The Western Indian Ocean biodiversity hotspot hosts a remarkable array of endemic species, but invasive alien species increasingly threaten its unique ecosystems. Lizards of the West African Agama agama species group are successful colonizers, with recent introductions to Grande Comore (Comoros Archipelago) and Reunion Island. Systematic revisions within the native range of the A. agama species group have left many of the introduced populations without clear identity. We used molecular methods to determine the identities of the Agama species introduced to Grande Comore and Reunion Island, define their respective likely origin, and assess body size characteristics for each island population. We identified Agama picticauda as the species present on both islands with likely origins in two distinct Western African regions. Agamas from Reunion Island had longer and wider heads with greater body weight than Grande Comore individuals. Sexual size dimorphism on both islands was driven by weight, with males being heavier than females. We provide foundations for further research on the ecology and impacts of A. picticauda on Western Indian Ocean islands and to aid in the development of targeted management strategies for controlling this invasive reptile.

Mead production and quality: A review of chemical and sensory mead quality evaluation with a focus on analytical methods - Claire E. Webster; David Barker; Rebecca C. Deed; Lisa I. Pilkington (Food Research International, 2025)

Intrinsic and environmental drivers of pairwise cohesion in wild Canis social groups - John F. Benson; David A. Keiter; Peter J. Mahoney; Benjamin L. Allen; Lee Allen; Francisco Álvares; Morgan L. Anderson; Shannon M. Barber‐Meyer; Adi Barocas; James C. Beasley; Linda Behrendorff; Jerrold L. Belant; et al. (Ecology, 2025)
Animals within social groups respond to costs and benefits of sociality by adjusting the proportion of time they spend in close proximity to other individuals in the group (cohesion). Variation in cohesion between individuals, in turn, shapes important group‐level processes such as subgroup formation and fission–fusion dynamics. Although critical to animal sociality, a comprehensive understanding of the factors influencing cohesion remains a gap in our knowledge of cooperative behavior in animals. We tracked 574 individuals from six species within the genus Canis in 15 countries on four continents with GPS telemetry to estimate the time that pairs of individuals within social groups spent in close proximity and test hypotheses regarding drivers of cohesion. Pairs of social canids ( Canis spp.) varied widely in the proportion of time they spent together (5%–100%) during seasonal monitoring periods relative to both intrinsic characteristics and environmental conditions. The majority of our data came from three species of wolves (gray wolves, eastern wolves, and red wolves) and coyotes. For these species, cohesion within social groups was greatest between breeding pairs and varied seasonally as the nature of cooperative activities changed relative to annual life history patterns. Across species, wolves were more cohesive than coyotes. For wolves, pairs were less cohesive in larger groups, and when suitable, small prey was present reflecting the constraints of food resources and intragroup competition on social associations. Pair cohesion in wolves declined with increased anthropogenic modification of the landscape and greater climatic variability, underscoring challenges for conserving social top predators in a changing world. We show that pairwise cohesion in social groups varies strongly both within and across Canis species, as individuals respond to changing ecological context defined by resources, competition, and anthropogenic disturbance. Our work highlights that cohesion is a highly plastic component of animal sociality that holds significant promise for elucidating ecological and evolutionary mechanisms underlying cooperative behavior.

Linking reservoir annual residence time to nitrogen deposition using paleolimnological techniques - Benjamin C. Webster; Matthew N. Waters; Stephen W. Golladay (Water Research, 2024)

The weather determined how ‘hot’ the tick paralysis season was in eastern Australia: 2018–2024 - Ernest J.M. Teo; Heather Russell; Tracey Lambert; Robert Webster; Amanda Yappa; Phillip McDonagh; Gavin Harper; Dayana Barker; Ryo Nakao; Stephen C. Barker (Veterinary Parasitology, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

Techno-economic assessment and carbon pricing analysis for economic feasibility of epoxidized sucrose soyate: A biobased thermoset resin - Shokoofeh Ghasemi; Mukund Sibi; Dean C. Webster; Ghasideh Pourhashem (Journal of Cleaner Production, 2024)

Fundamentals of wildlife dosimetry and lessons learned from a decade of measuring external dose rates in the field - Thomas G. Hinton; Donovan Anderson; Edda Bæk; Vikas C. Baranwal; James C. Beasley; Helen L. Bontrager; David Broggio; Justin Brown; Michael E. Byrne; Hannah C. Gerke; Hiroko Ishiniwa; Stacey L. Lance; et al. (Journal of Environmental Radioactivity, 2024)

First report of carnation Italian ringspot virus in Gypsophila in the United Kingdom - G. Webster; L. Frew; R. Ward; A. R. Fowkes; A. Skelton; V. Harju; I. P. Adams; S. McGreig; H. Pufal; C. Conyers; A. Fox (Journal of Plant Pathology, 2024)

Children's exposure to brominated flame retardants in the home: The TESIE study - Kate Hoffman; Xuening Tang; Ellen M. Cooper; Stephanie C. Hammel; Andreas Sjodin; Allison L. Phillips; Thomas F. Webster; Heather M. Stapleton (Environmental Pollution, 2024)

Characterizing northern white-cedar communities in harvested and unharvested lowland forests of Michigan, USA - Robin Michigiizhigookwe Clark; Christopher R. Webster; Laura S. Kenefic; Christel C. Kern; Rodney A. Chimner (Wetlands Ecology and Management, 2024)

Racial disparities in environmental exposures and SARS-CoV-2 infection rates: A detailed population-weighted analysis - Wenyan Xu; Bin Jiang; William C. Sullivan; Chris Webster; Yi Lu; Na Chen; Zhaowu Yu; Bin Chen (Sustainable Cities and Society, 2024)

What does climbing mean exactly? Assessing spatiotemporal gait characteristics of inclined locomotion in parrots - Melody W. Young; Clyde Webster; Daniel Tanis; Alissa F. Schurr; Christopher S. Hanna; Samantha K. Lynch; Aleksandra S. Ratkiewicz; Edwin Dickinson; Felix H. Kong; Michael C. Granatosky (Journal of Comparative Physiology A, 2024)

First report of Ornithogalum virus 3 in Galtonia candicans in the United Kingdom - J Dixon; K Chisnall; M Mynett; C Cunningham; G Webster; A Skelton; A. R. Fowkes; A Fox (Journal of Plant Pathology, 2023)

Protecting the invisible: Establishing guideline values for copper toxicity to marine microbiomes - Marie C. Thomas; Gretel Waugh; Inka Vanwonterghem; Nicole S. Webster; Christian Rinke; Rebecca Fisher; Heidi M. Luter; Andrew P. Negri (Science of The Total Environment, 2023)

Validation of key sponge symbiont pathways using genome‐centric metatranscriptomics - Paul A. O'Brien; Shangjin Tan; Pedro R. Frade; Steven J. Robbins; J. Pamela Engelberts; Sara C. Bell; Inka Vanwonterghem; David J. Miller; Nicole S. Webster; Guojie Zhang; David G. Bourne (Environmental Microbiology, 2023)
The sponge microbiome underpins host function through provision and recycling of essential nutrients in a nutrient poor environment. Genomic data suggest that carbohydrate degradation, carbon fixation, nitrogen metabolism, sulphur metabolism and supplementation of B‐vitamins are central microbial functions. However, validation beyond the genomic potential of sponge symbiont pathways is rarely explored. To evaluate metagenomic predictions, we sequenced the metagenomes and metatranscriptomes of three common coral reef sponges: Ircinia ramosa , Ircinia microconulosa and Phyllospongia foliascens . Multiple carbohydrate active enzymes were expressed by Poribacteria, Bacteroidota and Cyanobacteria symbionts, suggesting these lineages have a central role in assimilating dissolved organic matter. Expression of entire pathways for carbon fixation and multiple sulphur compound transformations were observed in all sponges. Gene expression for anaerobic nitrogen metabolism (denitrification and nitrate reduction) were more common than aerobic metabolism (nitrification), where only the I. ramosa microbiome expressed the nitrification pathway. Finally, while expression of the biosynthetic pathways for B‐vitamins was common, the expression of additional transporter genes was far more limited. Overall, we highlight consistencies and disparities between metagenomic and metatranscriptomic results when inferring microbial activity, while uncovering new microbial taxa that contribute to the health of their sponge host via nutrient exchange.

Evaluation of a sequential anaerobic-aerobic membrane bioreactor system for treatment of traditional and insensitive munitions constituents - Mark E. Fuller; Paul C. Hedman; Kung-Hui Chu; Todd S. Webster; Paul B. Hatzinger (Chemosphere, 2023)

Total infectome investigation of diphtheritic stomatitis in yellow-eyed penguins (Megadyptes antipodes) reveals a novel and abundant megrivirus - Janelle R. Wierenga; Rebecca M. Grimwood; Harry S. Taylor; Stuart Hunter; Lisa S. Argilla; Trudi Webster; Lauren Lim; Rebecca French; Hendrik Schultz; Fátima Jorge; Mihnea Bostina; Laura Burga; et al. (Veterinary Microbiology, 2023)

No evidence of sex ratio manipulation by black-throated blue warblers in response to food availability - Sara A. Kaiser; Kathryn C. Grabenstein; T. Scott Sillett; Michael S. Webster (Behavioral Ecology and Sociobiology, 2023)

Maze design: size and number of choices impact fish performance in cognitive assays - Nick A. R. Jones; Daphne Cortese; Amelia Munson; Helen C. Spence‐Jones; Zoe Storm; Shaun S. Killen; Ruth Bethel; Amy E. Deacon; Mike M. Webster; Libor Závorka (Journal of Fish Biology, 2023)
Although studies on fish cognition are increasing, consideration of how methodological details influence the ability to detect and measure performance is lagging. Here, in two separate experiments the authors compared latency to leave the start position, latency to make a decision, levels of participation and success rates (whether fish entered the rewarded chamber as first choice) across different physical designs. Experiments compared fish performance across (a) two sizes of T‐mazes, large and standard, and a plus‐maze, and (b) open choice arenas with either two or four doors. Fish in T‐mazes with longer arms took longer to leave the start chamber and were less likely to participate in a trial than fish in T‐mazes with shorter arms. The number of options, or complexity, in a maze significantly impacted success but did not necessarily impact behavioural measures, and did not impact the number of fish that reached a chamber. Fish in the plus‐maze had similar latencies to leave the start box and time to reach any chamber as fish in the same‐sized T‐maze but exhibited lower overall success. Similarly, in an open choice arena, increasing the number of options – doors to potential reward chambers − resulted in lower probability of success. There was an influence of reward position in the choice arena, with rewarded chambers closest to the sides of the arena resulting in lower latencies to enter and higher probability of decision success. Together the results allow the authors to offer practical suggestions towards optimal maze design for studies of fish cognition.

Low‐coverage whole genome sequencing for highly accurate population assignment: Mapping migratory connectivity in the American Redstart ( Setophaga ruticilla ) - Matthew G. DeSaix; Eric C. Anderson; Christen M. Bossu; Christine E. Rayne; Teia M. Schweizer; Nicholas J. Bayly; Darshan S. Narang; Julie C. Hagelin; H. Lisle Gibbs; James F. Saracco; Thomas W. Sherry; Michael S. Webster; et al. (Molecular Ecology, 2023)
Understanding the geographic linkages among populations across the annual cycle is an essential component for understanding the ecology and evolution of migratory species and for facilitating their effective conservation. While genetic markers have been widely applied to describe migratory connections, the rapid development of new sequencing methods, such as low‐coverage whole genome sequencing (lcWGS), provides new opportunities for improved estimates of migratory connectivity. Here, we use lcWGS to identify fine‐scale population structure in a widespread songbird, the American Redstart ( Setophaga ruticilla ), and accurately assign individuals to genetically distinct breeding populations. Assignment of individuals from the nonbreeding range reveals population‐specific patterns of varying migratory connectivity. By combining migratory connectivity results with demographic analysis of population abundance and trends, we consider full annual cycle conservation strategies for preserving numbers of individuals and genetic diversity. Notably, we highlight the importance of the Northern Temperate‐Greater Antilles migratory population as containing the largest proportion of individuals in the species. Finally, we highlight valuable considerations for other population assignment studies aimed at using lcWGS. Our results have broad implications for improving our understanding of the ecology and evolution of migratory species through conservation genomics approaches.

First report of eggplant mottled dwarf virus in Pittosporum tobria in the United Kingdom - Leanne Frew; C. Hogan; K. Andrews; A. Fowkes; A. Skelton; G. Webster; M. Dixon; C. Conyers; I. Adams; S. McGreig; A. Fox (Journal of Plant Pathology, 2023)

Drilling 1100-km-long seafloor ridges reveals how palaeoshorelines control carbonate shelf morphologies (North West Shelf, Australia) - Ulysse Lebrec; Rosine Riera; Michael O'Leary; Jody M. Webster; Yusuke Yokoyama; Luke A. Gliganic; Simon C. Lang; Victorien Paumard (Quaternary Science Reviews, 2023)

Geothermal energy production adversely affects a sensitive indicator species within sagebrush ecosystems in western North America - Peter S. Coates; Brian G. Prochazka; Shawn T. O'Neil; Sarah C. Webster; Shawn Espinosa; Mark A. Ricca; Steven R. Mathews; Michael Casazza; David J. Delehanty (Biological Conservation, 2023)

N-doped carbon nanospheres as selective fluorescent probes for mercury detection in contaminated aqueous media: chemistry, fluorescence probing, cell line patterning, and liver tissue interaction - Soheil Sojdeh; Ali Banitalebi Dehkordi; Alireza Badiei; Ali Zarrabi; Pooyan Makvandi; Milad Ashrafizadeh; Mohammad Reza Saeb; Eder C. Lima; Mohammad Rabiee; Mohsen Asadnia; Thomas J. Webster; Navid Rabiee (Environmental Science and Pollution Research, 2023)

Stakeholder Perspectives on the Roles of Science and Citizen Science in Chesapeake Bay Environmental Management - Suzanne E. Webster; William C. Dennison (Estuaries and Coasts, 2022)

The Influence of Landscape Structure on the Occurrence of Neospora caninum, Toxoplasma gondii, and Sarcocystis spp. in Free-Living Neotropical Primates - Elisandro O. dos Santos; Vinícius F. Klain; Sebastián B. Manrique; Isac Junior Roman; Helton F. dos Santos; Luís Antônio Sangioni; Fernanda S. F. Vogel; José Reck; Anelise Webster; Thamiris C. Padilha; Marco Antônio B. de Almeida; Edmilson dos Santos; et al. (Acta Parasitologica, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Grooming of fouling-release coatings to control marine fouling and determining how grooming affects the surface - Joseph Dahlgren; Lauren Foy; Kelli Hunsucker; Harrison Gardner; Geoff Swain; Shane J. Stafslien; Lyndsi Vanderwal; James Bahr; Dean C. Webster (Biofouling, 2022)

Genomic analysis of a parasite invasion: Colonization of the Americas by the blood fluke Schistosoma mansoni - Roy N. Platt; Winka Le Clec'h; Frédéric D. Chevalier; Marina McDew‐White; Philip T. LoVerde; Rafael Ramiro de Assis; Guilherme Oliveira; Safari Kinung'hi; Amadou Garba Djirmay; Michelle L. Steinauer; Anouk Gouvras; Muriel Rabone; et al. (Molecular Ecology, 2022)
Schistosoma mansoni , a snail‐borne, blood fluke that infects humans, was introduced into the Americas from Africa during the Trans‐Atlantic slave trade. As this parasite shows strong specificity to the snail intermediate host, we expected that adaptation to South American Biomphalaria spp. snails would result in population bottlenecks and strong signatures of selection. We scored 475,081 single nucleotide variants in 143 S. mansoni from the Americas (Brazil, Guadeloupe and Puerto Rico) and Africa (Cameroon, Niger, Senegal, Tanzania, and Uganda), and used these data to ask: (i) Was there a population bottleneck during colonization? (ii) Can we identify signatures of selection associated with colonization? (iii) What were the source populations for colonizing parasites? We found a 2.4‐ to 2.9‐fold reduction in diversity and much slower decay in linkage disequilibrium (LD) in parasites from East to West Africa. However, we observed similar nuclear diversity and LD in West Africa and Brazil, suggesting no strong bottlenecks and limited barriers to colonization. We identified five genome regions showing selection in the Americas, compared with three in West Africa and none in East Africa, which we speculate may reflect adaptation during colonization. Finally, we infer that unsampled populations from central African regions between Benin and Angola, with contributions from Niger, are probably the major source(s) for Brazilian S. mansoni . The absence of a bottleneck suggests that this is a rare case of a serendipitous invasion, where S. mansoni parasites were pre‐adapted to the Americas and able to establish with relative ease.

Durable siloxane-polyurethane coatings for mitigating freshwater mussel fouling - Teluka Pasan Galhenage; Shane J. Stafslien; Allen Skaja; Dean C. Webster (Biofouling, 2022)

Taking a macroscale perspective to improve understanding of shallow lake total phosphorus and chlorophyll a - Kendra Spence Cheruvelil; Katherine E. Webster; Katelyn B. S. King; Autumn C. Poisson; Tyler Wagner (Hydrobiologia, 2022)

A genomic and morphometric analysis of alpine bumblebees: Ongoing reductions in tongue length but no clear genetic component - Matthew J. Christmas; Julia C. Jones; Anna Olsson; Ola Wallerman; Ignas Bunikis; Marcin Kierczak; Kaitlyn M. Whitley; Isabel Sullivan; Jennifer C. Geib; Nicole E. Miller‐Struttmann; Matthew T. Webster (Molecular Ecology, 2022)
Over the last six decades, populations of the bumblebees Bombus sylvicola and Bombus balteatus in Colorado have experienced decreases in tongue length, a trait important for plant‐pollinator mutualisms. It has been hypothesized that this observation reflects selection resulting from shifts in floral composition under climate change. Here we used morphometrics and population genomics to determine whether morphological change is ongoing, investigate the genetic basis of morphological variation, and analyse population structure in these populations. We generated a genome assembly of B . balteatus . We then analysed whole‐genome sequencing data and morphometric measurements of 580 samples of both species from seven high‐altitude localities. Out of 281 samples originally identified as B . sylvicola , 67 formed a separate genetic cluster comprising a newly‐discovered cryptic species (“incognitus”). However, an absence of genetic structure within species suggests that gene flow is common between mountains. We found a significant decrease in tongue length between bees collected between 2012–2014 and in 2017, indicating that morphological shifts are ongoing. We did not discover any genetic associations with tongue length, but a SNP related to production of a proteolytic digestive enzyme was implicated in body size variation. We identified evidence of covariance between kinship and both tongue length and body size, which is suggestive of a genetic component of these traits, although it is possible that shared environmental effects between colonies are responsible. Our results provide evidence for ongoing modification of a morphological trait important for pollination and indicate that this trait probably has a complex genetic and environmental basis.

Protease-activated receptor 2 activation induces behavioural changes associated with depression-like behaviour through microglial-independent modulation of inflammatory cytokines - Serge Moudio; Ashleigh Willis; Karolina Pytka; Roua Abulkassim; Ros R. Brett; Jack F. Webster; Christian Wozny; Mark Barbour; Hui-Rong Jiang; David G. Watson; Josie C. van Kralingen; Scott M. MacKenzie; et al. (Psychopharmacology, 2022)
Rationale Major depressive disorder (MDD) is a leading cause of disability worldwide but currently prescribed treatments do not adequately ameliorate the disorder in a significant portion of patients. Hence, a better appreciation of its aetiology may lead to the development of novel therapies. Objectives In the present study, we have built on our previous findings indicating a role for protease-activated receptor-2 (PAR2) in sickness behaviour to determine whether the PAR2 activator, AC264613, induces behavioural changes similar to those observed in depression-like behaviour. Methods AC264613-induced behavioural changes were examined using the open field test (OFT), sucrose preference test (SPT), elevated plus maze (EPM), and novel object recognition test (NOR). Whole-cell patch clamping was used to investigate the effects of PAR2 activation in the lateral habenula with peripheral and central cytokine levels determined using ELISA and quantitative PCR. Results Using a blood–brain barrier (BBB) permeable PAR2 activator, we reveal that AC-264613 (AC) injection leads to reduced locomotor activity and sucrose preference in mice but is without effect in anxiety and memory-related tasks. In addition, we show that AC injection leads to elevated blood sera IL-6 levels and altered cytokine mRNA expression within the brain. However, neither microglia nor peripheral lymphocytes are the source of these altered cytokine profiles. Conclusions These data reveal that PAR2 activation results in behavioural changes often associated with depression-like behaviour and an inflammatory profile that resembles that seen in patients with MDD and therefore PAR2 may be a target for novel antidepressant therapies.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Occurrence of cucumber green mottle mosaic virus in Western Australia - Monica A. Kehoe; Craig Webster; Cuiping Wang; Roger A. C. Jones; Brenda A. Coutts (Australasian Plant Pathology, 2022)

Ontogenetic and spawning migration of Pacific halibut: a review - Piera Carpi; Timothy Loher; Lauri L. Sadorus; Joan E. Forsberg; Raymond A. Webster; Josep V. Planas; Andy Jasonowicz; Ian J. Stewart; Allan C. Hicks (Reviews in Fish Biology and Fisheries, 2021)

Evolution and connectivity influence the persistence and recovery of coral reefs under climate change in the Caribbean, Southwest Pacific, and Coral Triangle - Lisa C. McManus; Daniel L. Forrest; Eden Tekwa; Daniel E. Schindler; Madhavi A. Colton; Michael M. Webster; Timothy E. Essington; Stephen R. Palumbi; Peter J. Mumby; Malin L. Pinsky (Global Change Biology, 2021)
Corals are experiencing unprecedented decline from climate change‐induced mass bleaching events. Dispersal not only contributes to coral reef persistence through demographic rescue but can also hinder or facilitate evolutionary adaptation. Locations of reefs that are likely to survive future warming therefore remain largely unknown, particularly within the context of both ecological and evolutionary processes across complex seascapes that differ in temperature range, strength of connectivity, network size, and other characteristics. Here, we used eco‐evolutionary simulations to examine coral adaptation to warming across reef networks in the Caribbean, the Southwest Pacific, and the Coral Triangle. We assessed the factors associated with coral persistence in multiple reef systems to understand which results are general and which are sensitive to particular geographic contexts. We found that evolution can be critical in preventing extinction and facilitating the long‐term recovery of coral communities in all regions. Furthermore, the strength of immigration to a reef (destination strength) and current sea surface temperature robustly predicted reef persistence across all reef networks and across temperature projections. However, we found higher initial coral cover, slower recovery, and more evolutionary lag in the Coral Triangle, which has a greater number of reefs and more larval settlement than the other regions. We also found the lowest projected future coral cover in the Caribbean. These findings suggest that coral reef persistence depends on ecology, evolution, and habitat network characteristics, and that, under an emissions stabilization scenario (RCP 4.5), recovery may be possible over multiple centuries.

Examining the impact of the Great Barrier Reef on tsunami propagation using numerical simulations - Mandi C. Thran; Sascha Brune; Jody M. Webster; Dale Dominey-Howes; Daniel Harris (Natural Hazards, 2021)

Environmental controls on holocene reef development along the eastern brazilian margin - Belinda Dechnik; Alex C. Bastos; Laura S. Vieira; Jody M. Webster; Stewart Fallon; Yusuke Yokoyama; Juan-Carlos Braga; Manuel A. Pereira; Luke Nothdurft; Kelsey Sanborn; Rodrigo L. Moura; Gilberto Amado-filho (Coral Reefs, 2021)

Evolution reverses the effect of network structure on metapopulation persistence - Lisa C. McManus; Eden Tekwa; Daniel E. Schindler; Timothy E. Walsworth; Madhavi A. Colton; Michael M. Webster; Timothy E. Essington; Daniel L. Forrest; Stephen R. Palumbi; Peter J. Mumby; Malin L. Pinsky (Ecology, 2021)
Global environmental change is challenging species with novel conditions, such that demographic and evolutionary trajectories of populations are often shaped by the exchange of organisms and alleles across landscapes. Current ecological theory predicts that random networks with dispersal shortcuts connecting distant sites can promote persistence when there is no capacity for evolution. Here, we show with an eco‐evolutionary model that dispersal shortcuts across environmental gradients instead hinder persistence for populations that can evolve because long‐distance migrants bring extreme trait values that are often maladaptive, short‐circuiting the adaptive response of populations to directional change. Our results demonstrate that incorporating evolution and environmental heterogeneity fundamentally alters theoretical predictions regarding persistence in ecological networks.

Surface modifying amphiphilic additives and their effect on the fouling-release performance of siloxane-polyurethane coatings - Jackson Benda; Shane Stafslien; Lyndsi Vanderwal; John A. Finlay; Anthony S. Clare; Dean C. Webster (Biofouling, 2021)

Individual behavioural traits not social context affects learning about novel objects in archerfish - Nick A. R. Jones; Helen C. Spence-Jones; Mike Webster; Luke Rendell (Behavioral Ecology and Sociobiology, 2021)
Learning can enable rapid behavioural responses to changing conditions but can depend on the social context and behavioural phenotype of the individual. Learning rates have been linked to consistent individual differences in behavioural traits, especially in situations which require engaging with novelty, but the social environment can also play an important role. The presence of others can modulate the effects of individual behavioural traits and afford access to social information that can reduce the need for ‘risky’ asocial learning. Most studies of social effects on learning are focused on more social species; however, such factors can be important even for less-social animals, including non-grouping or facultatively social species which may still derive benefit from social conditions. Using archerfish, Toxotes chatareus , which exhibit high levels of intra-specific competition and do not show a strong preference for grouping, we explored the effect of social contexts on learning. Individually housed fish were assayed in an ‘open-field’ test and then trained to criterion in a task where fish learnt to shoot a novel cue for a food reward—with a conspecific neighbour visible either during training, outside of training or never (full, partial or no visible presence). Time to learn to shoot the novel cue differed across individuals but not across social context. This suggests that social context does not have a strong effect on learning in this non-obligatory social species; instead, it further highlights the importance that inter-individual variation in behavioural traits can have on learning. Significance statement Some individuals learn faster than others. Many factors can affect an animal’s learning rate—for example, its behavioural phenotype may make it more or less likely to engage with novel objects. The social environment can play a big role too—affecting learning directly and modifying the effects of an individual’s traits. Effects of social context on learning mostly come from highly social species, but recent research has focused on less-social animals. Archerfish display high intra-specific competition, and our study suggests that social context has no strong effect on their learning to shoot novel objects for rewards. Our results may have some relevance for social enrichment and welfare of this increasingly studied species, suggesting there are no negative effects of short- to medium-term isolation of this species—at least with regards to behavioural performance and learning tasks.

Persistent Hydrodynamic Cues Elicit Orientation-Specific Behavioral Sensitivities and Kinematic Responses in Dispersed Crab Larvae - Aaron C. True; Donald R. Webster; Marc J. Weissburg; Jeannette Yen (Frontiers in Marine Science, 2020)

Translational studies of intravenous and intracerebroventricular routes of administration for CNS cellular biodistribution for BMN 250, an enzyme replacement therapy for the treatment of Sanfilippo type B - Anita Grover; Danielle Crippen-Harmon; Lacey Nave; Jon Vincelette; Jill C. M. Wait; Andrew C. Melton; Roger Lawrence; Jillian R. Brown; Katherine A. Webster; Bryan K. Yip; Brian Baridon; Catherine Vitelli; et al. (Drug Delivery and Translational Research, 2020)
BMN 250 is being developed as enzyme replacement therapy for Sanfilippo type B, a primarily neurological rare disease, in which patients have deficient lysosomal alpha- N -acetylglucosaminidase (NAGLU) enzyme activity. BMN 250 is taken up in target cells by the cation-independent mannose 6-phosphate receptor (CI-MPR, insulin-like growth factor 2 receptor), which then facilitates transit to the lysosome. BMN 250 is dosed directly into the central nervous system via the intracerebroventricular (ICV) route, and the objective of this work was to compare systemic intravenous (IV) and ICV delivery of BMN 250 to confirm the value of ICV dosing. We first assess the ability of enzyme to cross a potentially compromised blood–brain barrier in the Naglu −/− mouse model and then assess the potential for CI-MPR to be employed for receptor-mediated transport across the blood–brain barrier. In wild-type and Naglu −/− mice, CI-MPR expression in brain vasculature is high during the neonatal period but virtually absent by adolescence. In contrast, CI-MPR remains expressed through adolescence in non-affected non-human primate and human brain vasculature. Combined results from IV administration of BMN 250 in Naglu −/− mice and IV and ICV administration in healthy juvenile non-human primates suggest a limitation to therapeutic benefit from IV administration because enzyme distribution is restricted to brain vascular endothelial cells: enzyme does not reach target neuronal cells following IV administration, and pharmacological response following IV administration is likely restricted to clearance of substrate in endothelial cells. In contrast, ICV administration enables central nervous system enzyme replacement with biodistribution to target cells.

Improved Pastures Support Early Indicators of Soil Restoration in Low-input Agroecosystems of Nicaragua - Emily Webster; Amélie C. M. Gaudin; Mirjam Pulleman; Pablo Siles; Steven J. Fonte (Environmental Management, 2019)

Paleoshorelines and lowstand sedimentation on subtropical shelves: a case study from the Fraser Shelf, Australia - T. U. Passos; J. M. Webster; J. C. Braga; D. Voelker; W. Renema; R. J. Beaman; L. D. Nothdurft; G. Hinestrosa; S. Clarke; Y. Yokoyama; R. L. Barcellos; M. A. Kinsela; et al. (Australian Journal of Earth Sciences, 2019)

Morphology and sedimentology of the shelf-upper slope transition in the Abrolhos continental shelf (east Brazilian margin) - Danielle P. D’Agostini; Alex C. Bastos; Gilberto M. Amado-Filho; Claudia G. Vilela; Thaís C. S. Oliveira; Jody M. Webster; Rodrigo L. Moura (Geo-Marine Letters, 2019)

Evidence of long-distance dispersal of a gray wolf from the Chernobyl Exclusion Zone - Michael E. Byrne; Sarah C. Webster; Stacey L. Lance; Cara N. Love; Thomas G. Hinton; Dmitry Shamovich; James C. Beasley (European Journal of Wildlife Research, 2018)

New diagnostic descriptions and distribution information for Shepherd's beaked whale ( Tasmacetus shepherdi ) off Southern Australia and New Zealand - David M. Donnelly; Paul Ensor; Peter Gill; Rohan H. Clarke; Karen Evans; Michael C. Double; Trudi Webster; Will Rayment; Natalie T. Schmitt (Marine Mammal Science, 2018)

Reef invertebrate viromics: diversity, host specificity and functional capacity - Patrick W. Laffy; Elisha M. Wood‐Charlson; Dmitrij Turaev; Sabrina Jutz; Cecilia Pascelli; Emmanuelle S. Botté; Sara C. Bell; Tyler E. Peirce; Karen D. Weynberg; Madeleine J. H. van Oppen; Thomas Rattei; Nicole S. Webster (Environmental Microbiology, 2018)
Summary Recent metagenomic analyses have revealed a high diversity of viruses in the pelagic ocean and uncovered clear habitat‐specific viral distribution patterns. Conversely, similar insights into the composition, host specificity and function of viruses associated with marine organisms have been limited by challenges associated with sampling and computational analysis. Here, we performed targeted viromic analysis of six coral reef invertebrate species and their surrounding seawater to deliver taxonomic and functional profiles of viruses associated with reef organisms. Sponges and corals' host species‐specific viral assemblages with low sequence identity to known viral genomes. While core viral genes involved in capsid formation, tail structure and infection mechanisms were observed across all reef samples, auxiliary genes including those involved in herbicide resistance and viral pathogenesis pathways such as host immune suppression were differentially enriched in reef hosts. Utilising a novel OTU based assessment, we also show a prevalence of dsDNA viruses belonging to the Mimiviridae , Caudovirales and Phycodnaviridae in reef environments and further highlight the abundance of ssDNA viruses belonging to the Circoviridae , Parvoviridae , Bidnaviridae and Microviridae in reef invertebrates. These insights into coral reef viruses provide an important framework for future research into how viruses contribute to the health and evolution of reef organisms.

Copepod avoidance of thin chemical layers of harmful algal compounds - A. C. True; D. R. Webster; M. J. Weissburg; J. Yen (Limnology and Oceanography, 2018)
In a physical model of a thin planktonic layer, the estuarine copepod Acartia tonsa strongly avoided weakly stratified layers of dissolved chemical compounds from the harmful dinoflagellate Karenia brevis . Chemical‐induced changes in swimming kinematics allowed copepods to effectively avoid the layer and surrounding volume, highlighting the relevance of harmful alga‐grazer interactions at a distance that involve dissolved chemical signals. Avoidance increased significantly with increasing chemical concentration representative of a range of ecologically relevant bloom conditions (1–10 4 cells/mL equivalent). Under mid to maximal bloom conditions, Acartia displayed visually and hydrodynamically conspicuous avoidance jumps featuring large, rapid displacements with swimming speeds near those reported for predatory escape reactions. Previous findings show K. brevis is both toxic and nutritionally inadequate to A. tonsa when ingested and that exposure to dissolved chemical compounds likely rapidly suppresses effective sampling and grazing behaviors. Thus, copepods have strong incentive to sense and avoid nearby, spatially discrete patches of toxic algae in order to improve fitness by avoiding exposure and/or ingestion and associated negative impacts. Our results suggest harmful alga not only produce deleterious physiological effects in copepod grazers, but chemical‐induced behavioral responses also likely alter grazer distributions and top‐down control via avoidance reactions (reduced harmful alga‐grazer encounter rates). Additionally, predator‐prey encounter rates at higher trophic levels are likely enhanced via significant changes in copepod swimming kinematics. These combined mechanisms could protect and sustain harmful blooms contained in subsurface thin layers until blooms reach critical mass and produce widespread impacts at the ecosystem level, the “cryptic bloom” effect.

Bird community responses to afforested eucalyptus plantations in the Argentine pampas - Colin C. Phifer; Jessie L. Knowlton; Christopher R. Webster; David J. Flaspohler; Julian A. Licata (Biodiversity and Conservation, 2017)

Multiple hypotheses explain variation in extra‐pair paternity at different levels in a single bird family - Lyanne Brouwer; Martijn van de Pol; Nataly Hidalgo Aranzamendi; Glen Bain; Daniel T. Baldassarre; Lesley C. Brooker; Michael G. Brooker; Diane Colombelli‐Négrel; Erik Enbody; Kurt Gielow; Michelle L. Hall; Allison E. Johnson; et al. (Molecular Ecology, 2017)
Extra‐pair paternity ( EPP ), where offspring are sired by a male other than the social male, varies enormously both within and among species. Trying to explain this variation has proved difficult because the majority of the interspecific variation is phylogenetically based. Ideally, variation in EPP should be investigated in closely related species, but clades with sufficient variation are rare. We present a comprehensive multifactorial test to explain variation in EPP among individuals in 20 populations of nine species over 89 years from a single bird family (Maluridae). Females had higher EPP in the presence of more helpers, more neighbours or if paired incestuously. Furthermore, higher EPP occurred in years with many incestuous pairs, populations with many helpers and species with high male density or in which males provide less care. Altogether, these variables accounted for 48% of the total and 89% of the interspecific and interpopulation variation in EPP . These findings indicate why consistent patterns in EPP have been so challenging to detect and suggest that a single predictor is unlikely to account for the enormous variation in EPP across levels of analysis. Nevertheless, it also shows that existing hypotheses can explain the variation in EPP well and that the density of males in particular is a good predictor to explain variation in EPP among species when a large part of the confounding effect of phylogeny is excluded.

Drivers of nitrogen transfer in stream food webs across continents - Beth C. Norman; Matt R. Whiles; Sarah M. Collins; Alexander S. Flecker; Steve K. Hamilton; Sherri L. Johnson; Emma J. Rosi; Linda R. Ashkenas; William B. Bowden; Chelsea L. Crenshaw; Todd Crowl; Walter K. Dodds; et al. (Ecology, 2017)
Studies of trophic‐level material and energy transfers are central to ecology. The use of isotopic tracers has now made it possible to measure trophic transfer efficiencies of important nutrients and to better understand how these materials move through food webs. We analyzed data from thirteen 15 N‐ammonium tracer addition experiments to quantify N transfer from basal resources to animals in headwater streams with varying physical, chemical, and biological features. N transfer efficiencies from primary uptake compartments (PUCs; heterotrophic microorganisms and primary producers) to primary consumers was lower (mean 11.5%, range 100%). Total N transferred (as a rate) was greater in streams with open compared to closed canopies and overall N transfer efficiency generally followed a similar pattern, although was not statistically significant. We used principal component analysis to condense a suite of site characteristics into two environmental components. Total N uptake rates among trophic levels were best predicted by the component that was correlated with latitude, DIN:SRP, GPP:ER, and percent canopy cover. N transfer efficiency did not respond consistently to environmental variables. Our results suggest that canopy cover influences N movement through stream food webs because light availability and primary production facilitate N transfer to higher trophic levels.

An individual-based model of chaparral vegetation response to frequent wildfires - Timothy A. Lucas; Reanna A. Doña; Wancen Jiang; Garrett C. Johns; Dayna J. Mann; Cassandra Seubert; Noah B. C. Webster; Charlotte H. Willens; Stephen D. Davis (Theoretical Ecology, 2017)

Research priorities for managing the impacts and dependencies of business upon food, energy, water and the environment - Jonathan M. H. Green; Gemma R. Cranston; William J. Sutherland; Hannah R. Tranter; Sarah J. Bell; Tim G. Benton; Eva Blixt; Colm Bowe; Sarah Broadley; Andrew Brown; Chris Brown; Neil Burns; et al. (Sustainability Science, 2017)

Raccoons (Procyon lotor) as Sentinels of Trace Element Contamination and Physiological Effects of Exposure to Coal Fly Ash - Felipe Hernández; Ricki E. Oldenkamp; Sarah Webster; James C. Beasley; Lisa L. Farina; Samantha M. Wisely (Archives of Environmental Contamination and Toxicology, 2017)

Characterization of 14 polymorphic microsatellite loci developed for an Afrotherian species endemic to southern Africa, Elephantulus myurus (Macroscelidea: Macroscelididae) - Sasha Hoffmann; Heather J. Webster; Peter R. Teske; Heike Lutermann; Nigel C. Bennett; Bettine Jansen van Vuuren (Applied Entomology and Zoology, 2017)

On wave–current interaction by the Green–Naghdi equations in shallow water - W. Y. Duan; K. Zheng; B. B. Zhao; Z. Demirbilek; R. C. Ertekin; W. C. Webster (Natural Hazards, 2016)

Comparison of laboratory and field testing performance evaluations of siloxane-polyurethane fouling-release marine coatings - Shane J. Stafslien; Stacy Sommer; Dean C. Webster; Rajan Bodkhe; Robert Pieper; Justin Daniels; Lyndsi Vander Wal; Maureen C. Callow; James A. Callow; Emily Ralston; Geoff Swain; Lenora Brewer; et al. (Biofouling, 2016)

Evidence for a Regime Shift in Nitrogen Export from a Forested Watershed - J. R. Webster; J. D. Knoepp; W. T. Swank; C. F. Miniat (Ecosystems, 2016)

Sedimentology, structure and age estimate of five continental slope submarine landslides, eastern Australia - S. Clarke; T. Hubble; J. Webster; D. Airey; E. De Carli; C. Ferraz; P. Reimer; R. Boyd; J. Keene (Australian Journal of Earth Sciences, 2016)

Magmatic–hydrothermal fluids and volatile metals in the Spirit Lake pluton and Margaret Cu–Mo porphyry system, SW Washington, USA - Alexander A. Iveson; James D. Webster; Michael C. Rowe; Owen K. Neill (Contributions to Mineralogy and Petrology, 2016)

Artificial microtopography and herbivory protection facilitates wetland tree (Thuja occidentalis L.) survival and growth in created wetlands - Laura C. Kangas; Rose Schwartz; Michael R. Pennington; Christopher R. Webster; Rodney A. Chimner (New Forests, 2016)

Assessment of toxicity and coagulopathy of brodifacoum in Japanese quail and testing in wild owls - Kirstin H. Webster; Kendal E. Harr; Darin C. Bennett; Tony D. Williams; Kimberly M. Cheng; France Maisonneuve; John E. Elliott (Ecotoxicology, 2015)

CMV in the gut: a critical review of CMV detection in the immunocompetent host with colitis - A. L. Goodman; C. D. Murray; J. Watkins; P. D. Griffiths; D. P. Webster (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

You are not always what we think you eat: selective assimilation across multiple whole‐stream isotopic tracer studies - W. K. Dodds; S. M. Collins; S. K. Hamilton; J. L. Tank; S. Johnson; J. R. Webster; K. S. Simon; M. R. Whiles; H. M. Rantala; W. H. McDowell; S. D. Peterson; T. Riis; et al. (Ecology, 2014)
Analyses of 21 15 N stable isotope tracer experiments, designed to examine food web dynamics in streams around the world, indicated that the isotopic composition of food resources assimilated by primary consumers (mostly invertebrates) poorly reflected the presumed food sources. Modeling indicated that consumers assimilated only 33–50% of the N available in sampled food sources such as decomposing leaves, epilithon, and fine particulate detritus over feeding periods of weeks or more. Thus, common methods of sampling food sources consumed by animals in streams do not sufficiently reflect the pool of N they assimilate. Isotope tracer studies, combined with modeling and food separation techniques, can improve estimation of N pools in food sources that are assimilated by consumers. Food web studies that use putative food samples composed of actively cycling (more readily assimilable) and refractory (less assimilable) N fractions may draw erroneous conclusions about diets, N turnover, and trophic linkages of consumers. By extension, food web studies using stoichiometric or natural abundance approaches that rely on an accurate description of food‐source composition could result in errors when an actively cycling pool that is only a fraction of the N pool in sampled food resources is not accounted for.

Occupational Health Among Latino Horse and Crop Workers in Kentucky: The Role of Work Organization Factors - Jennifer E. Swanberg; Jessica Miller Clouser; Steven R. Browning; Susan C. Westneat; Mary Webster Marsh (Journal of Agromedicine, 2014)

Neuromuscular junction abnormalities in DNM2-related centronuclear myopathy - Elizabeth M. Gibbs; Nigel F. Clarke; Kristy Rose; Emily C. Oates; Richard Webster; Eva L. Feldman; James J. Dowling (Journal of Molecular Medicine, 2013)

Genotypic variation in the ability of wheat roots to penetrate wax layers - W. R. Whalley; I. C. Dodd; C. W. Watts; C. P. Webster; A. L. Phillips; J. Andralojc; R. P. White; W. J. Davies; M. A. J. Parry (Plant and Soil, 2013)

Sodium bicarbonate supplementation improves hypertrophy-type resistance exercise performance - Benjamin M. Carr; Michael J. Webster; Joseph C. Boyd; Geoffrey M. Hudson; Timothy P. Scheett (European Journal of Applied Physiology, 2013)

Mevalocidin: A Novel, Phloem Mobile Phytotoxin from Fusarium DA056446 and Rosellinia DA092917 - B. Clifford Gerwick; William K. Brewster; Gerrit J. deBoer; Steve C. Fields; Paul R. Graupner; Donald R. Hahn; Cedric J. Pearce; Paul R. Schmitzer; Jeffery D. Webster (Journal of Chemical Ecology, 2013)

Diversity of Scleractinia and Octocorallia in the mesophotic zone of the Great Barrier Reef, Australia - T. C. L. Bridge; K. E. Fabricius; P. Bongaerts; C. C. Wallace; P. R. Muir; T. J. Done; J. M. Webster (Coral Reefs, 2012)

Zucchini yellow mosaic virus: biological properties, detection procedures and comparison of coat protein gene sequences - B. A. Coutts; M. A. Kehoe; C. G. Webster; S. J. Wylie; R. A. C. Jones (Archives of Virology, 2011)

Indigenous and introduced potyviruses of legumes and Passiflora spp. from Australia: biological properties and comparison of coat protein nucleotide sequences - Brenda A. Coutts; Monica A. Kehoe; Craig G. Webster; Stephen J. Wylie; Roger A. C. Jones (Archives of Virology, 2011)

Enrichment culture of CSF is of limited value in the diagnosis of neonatal meningitis - S. H. Chaudhry; D. Wagstaff; A. Gupta; I. C. Bowler; D. P. Webster (European Journal of Clinical Microbiology & Infectious Diseases, 2011)

Topography, substratum and benthic macrofaunal relationships on a tropical mesophotic shelf margin, central Great Barrier Reef, Australia - T. C. L. Bridge; T. J. Done; R. J. Beaman; A. Friedman; S. B. Williams; O. Pizarro; J. M. Webster (Coral Reefs, 2011)

A preliminary study on the properties and fouling-release performance of siloxane–polyurethane coatings prepared from poly(dimethylsiloxane) (PDMS) macromers - Stacy Sommer; Abdullah Ekin; Dean C. Webster; Shane J. Stafslien; Justin Daniels; Lyndsi J. VanderWal; Stephanie E.M. Thompson; Maureen E. Callow; James A. Callow (Biofouling, 2010)

The maximum age of Hawaiian terrestrial lineages: geological constraints from Kōko Seamount - David A. Clague; Juan C. Braga; Davide Bassi; Paul D. Fullagar; Willem Renema; Jody M. Webster (Journal of Biogeography, 2010)
Aim To determine if Kōko Seamount submerged below sea level before Kure Island and Pearl and Hermes Reef formed, resulting in a period in which there were no extant islands. A period with no islands would eliminate prior terrestrial and shallow marine biotas that could migrate from island to island and require a restart of colonization from distant shores to populate the younger islands of the Hawaiian volcanic chain. Location Emperor Seamount Chain, north‐central Pacific Ocean. Methods We estimate subsidence rates for Kōko Seamount using ages determined from fossil large foraminifera and Sr‐isotopes, and maximum depths using palaeodepth estimates based on coralline algae. These data are combined with palaeolatitude changes as the Pacific Plate moved northwards, sea level variations, and sea surface temperature variations at the seamount through time to reconstruct the time and causes of submergence. Results Rounded carbonate clasts include three facies: zooxanthelate corals, bioclastic packstones to rudstones, and rhodolith floatstones. Two rudstones contain relatively deep‐water, coralline algal rhodoliths and large foraminifera indicative of Aquitanian (20.4–20 Ma) and Burdigalian (20–16 Ma) stages of the Early Miocene, consistent with Sr‐isotope ages of algae and one sample of large foraminifera. Corals grew on Kōko Seamount from c . 50 to 27.1 ± 0.4 Ma, the youngest Sr‐isotope age of a coral sample. These shallow, warm‐water coral reefs came under increasing stress as the volcano subsided at 0.012 ± 0.003 mm yr −1 , and migrated northwards, and as global climate cooled. The summit submerged and shallow coral reef growth ceased before 29 Ma, probably around 33 Ma. The volcano continued its slow subsidence, and deep‐water carbonates accumulated until they too were unable to keep pace, dying out at c . 16 Ma. Main conclusions The final submergence of the summit of Kōko Seamount by about 33 Ma confirms that biota on older Hawaiian–Emperor Islands could not have migrated from island to island along the entire chain to eventually colonize the present Hawaiian Islands. There was a period between at least 33 and 29 Ma in which no islands existed, and distant colonization had to repopulate the younger portion of the Hawaiian chain, which began to emerge between about 29 and 23 Ma.

Community dynamics of Pleistocene coral reefs during alternative climatic regimes - Danika Tager; Jody M. Webster; Donald C. Potts; Willem Renema; Juan C. Braga; John M. Pandolfi (Ecology, 2010)
Reef ecosystems built during successive periods of Pleistocene sea level rise have shown remarkable persistence in coral community structure, but little is known of the ecological characteristics of reef communities during periods of low sea stands or sea level falls. We sampled the relative species abundance of coral, benthic foraminifera, and calcareous red algae communities from eight submerged coral reefs in the Huon Gulf, Papua New Guinea, which formed during successive sea level fall and lowstand periods over the past ∼416 kyr. We found that dissimilarity in coral species composition increased significantly with increasing time between reef‐building events. However, neither coral diversity nor the taxonomic composition of benthic foraminifera and calcareous red algae assemblages varied significantly over time. The taxonomic composition of coral communities from lowstand reefs was significantly different from that of highstand reefs previously reported from the nearby Huon Peninsula. We interpret the community composition and temporal dynamics of lowstand reefs as a result of shifting energy regimes in the Huon Gulf, and differences between low and highstand reefs as a result of differences in the interaction between biotic and environmental factors between the Huon Gulf and Huon Peninsula. Regardless of the exact processes driving these trends, our study represents the first glimpse into the ecological dynamics of coral reefs during low sea level stands when climatic conditions for reef growth were much different and less optimal than during previously studied highstand periods.

Characterisation and expression of SPLUNC2, the human orthologue of rodent parotid secretory protein - Lynne Bingle; Frances A. Barnes; Hayley Lunn; Maslinda Musa; Steve Webster; C. W. Ian Douglas; Simon S. Cross; Alec S. High; Colin D. Bingle (Histochemistry and Cell Biology, 2009)

Application of a serial extended forecast experiment using the ECMWF model to interpret the predictive skill of tropical intraseasonal variability - P. A. Agudelo; C. D. Hoyos; P. J. Webster; J. A. Curry (Climate Dynamics, 2009)

Nitrate removal in stream ecosystems measured by 15N addition experiments: Total uptake - Robert O. Hall; Jennifer L. Tank; Daniel J. Sobota; Patrick J. Mulholland; Jonathan M. O'Brien; Walter K. Dodds; Jackson R. Webster; H. Maurice Valett; Geoffrey C. Poole; Bruce J. Peterson; Judy L. Meyer; William H. McDowell; et al. (Limnology and Oceanography, 2009)
We measured uptake length of 15 NO 3 − in 72 streams in eight regions across the United States and Puerto Rico to develop quantitative predictive models on controls of NO 3 − uptake length. As part of the Lotic Intersite Nitrogen eXperiment II project, we chose nine streams in each region corresponding to natural (reference), suburban‐urban, and agricultural land uses. Study streams spanned a range of human land use to maximize variation in NO 3 − concentration, geomorphology, and metabolism. We tested a causal model predicting controls on NO 3 − uptake length using structural equation modeling. The model included concomitant measurements of ecosystem metabolism, hydraulic parameters, and nitrogen concentration. We compared this structural equation model to multiple regression models which included additional biotic, catchment, and riparian variables. The structural equation model explained 79% of the variation in log uptake length ( S Wtot ). Uptake length increased with specific discharge ( Q/w ) and increasing NO 3 − concentrations, showing a loss in removal efficiency in streams with high NO 3 − concentration. Uptake lengths shortened with increasing gross primary production, suggesting autotrophic assimilation dominated NO 3 − removal. The fraction of catchment area as agriculture and suburban‐urban land use weakly predicted NO 3 − uptake in bivariate regression, and did improve prediction in a set of multiple regression models. Adding land use to the structural equation model showed that land use indirectly affected NO 3 − uptake lengths via directly increasing both gross primary production and NO 3 − concentration. Gross primary production shortened S Wtot , while increasing NO 3 − lengthened S Wtot resulting in no net effect of land use on NO 3 − removal.

Nitrate removal in stream ecosystems measured by 15N addition experiments: Denitrification - Patrick J. Mulholland; Robert O. Hall; Daniel J. Sobota; Walter K. Dodds; Stuart E. G. Findlay; Nancy B. Grimm; Stephen K. Hamilton; William H. McDowell; Jonathan M. O'Brien; Jennifer L. Tank; Linda R. Ashkenas; Lee W. Cooper; et al. (Limnology and Oceanography, 2009)
We measured denitrification rates using a field 15 NO 3 − tracer‐addition approach in a large, cross‐site study of nitrate uptake in reference, agricultural, and suburban‐urban streams. We measured denitrification rates in 49 of 72 streams studied. Uptake length due to denitrification ( S Wden n) ranged from 89 m to 184 km (median of 9050 m) and there were no significant differences among regions or land‐use categories, likely because of the wide range of conditions within each region and land use. N 2 production rates far exceeded N 2 O production rates in all streams. The fraction of total NO 3 − removal from water due to denitrification ranged from 0.5% to 100% among streams (median of 16%), and was related to NH 4 + concentration and ecosystem respiration rate (ER). Multivariate approaches showed that the most important factors controlling S Wden were specific discharge (discharge / width) and NO 3 − concentration (positive effects), and ER and transient storage zones (negative effects). The relationship between areal denitrification rate ( U den ) and NO 3 − concentration indicated a partial saturation effect. A power function with an exponent of 0.5 described this relationship better than a Michaelis‐Menten equation. Although U den increased with increasing NO 3 − concentration, the efficiency of NO 3 − removal from water via denitrification declined, resulting in a smaller proportion of streamwater NO 3 − load removed over a given length of stream. Regional differences in stream denitrification rates were small relative to the proximate factors of NO 3 − concentration and ecosystem respiration rate, and land use was an important but indirect control on denitrification in streams, primarily via its effect on NO 3 − concentration.

Subsurface microbiology and biogeochemistry of a deep, cold‐water carbonate mound from the Porcupine Seabight (IODP Expedition 307) - Gordon Webster; Anna Blazejak; Barry A. Cragg; Axel Schippers; Henrik Sass; Joachim Rinna; Xiaohong Tang; Falko Mathes; Timothy G. Ferdelman; John C. Fry; Andrew J. Weightman; R. John Parkes (Environmental Microbiology, 2009)
Summary The Porcupine Seabight Challenger Mound is the first carbonate mound to be drilled (∼270 m) and analyzed in detail microbiologically and biogeochemically. Two mound sites and a non‐mound Reference site were analyzed with a range of molecular techniques [catalyzed reporter deposition‐fluorescence in situ hybridization (CARD‐FISH), quantitative PCR (16S rRNA and functional genes, dsrA and mcrA ), and 16S rRNA gene PCR‐DGGE] to assess prokaryotic diversity, and this was compared with the distribution of total and culturable cell counts, radiotracer activity measurements and geochemistry. There was a significant and active prokaryotic community both within and beneath the carbonate mound. Although total cell numbers at certain depths were lower than the global average for other subseafloor sediments and prokaryotic activities were relatively low (iron and sulfate reduction, acetate oxidation, methanogenesis) they were significantly enhanced compared with the Reference site. In addition, there was some stimulation of prokaryotic activity in the deepest sediments (Miocene, > 10 Ma) including potential for anaerobic oxidation of methane activity below the mound base. Both Bacteria and Archaea were present, with neither dominant, and these were related to sequences commonly found in other subseafloor sediments. With an estimate of some 1600 mounds in the Porcupine Basin alone, carbonate mounds may represent a significant prokaryotic subseafloor habitat.

ENDOGENOUS AND EXOGENOUS CONTROL OF ECOSYSTEM FUNCTION: N CYCLING IN HEADWATER STREAMS - H. M. Valett; S. A. Thomas; P. J. Mulholland; J. R. Webster; C. N. Dahm; C. S. Fellows; C. L. Crenshaw; C. G. Peterson (Ecology, 2008)
Allochthonous inputs act as resource subsidies to many ecosystems, where they exert strong influences on metabolism and material cycling. At the same time, metabolic theory proposes endogenous thermal control independent of resource supply. To address the relative importance of exogenous and endogenous influences, we quantified spatial and temporal variation in ecosystem metabolism and nitrogen (N) uptake using seasonal releases of 15 N as nitrate in six streams differing in riparian–stream interaction and metabolic character. Nitrate removal was quantified using a nutrient spiraling approach based on measurements of downstream decline in 15 N flux. Respiration ( R ) and gross primary production (GPP) were measured with whole‐stream diel oxygen budgets. Uptake and metabolism metrics were addressed as z scores relative to site means to assess temporal variation. In open‐canopied streams, areal uptake ( U ; μg N·m −2 ·s −1 ) was closely related to GPP, metabolic rates increased with temperature, and R was accurately predicted by metabolic scaling relationships. In forested streams, N spiraling was not related to GPP; instead, uptake velocity ( v f ; mm/s) was closely related to R . In contrast to open‐canopied streams, N uptake and metabolic activity were negatively correlated to temperature and poorly described by scaling laws. We contend that streams differ along a gradient of exogenous and endogenous control that relates to the relative influences of resource subsidies and in‐stream energetics as determinants of seasonal patterns of metabolism and N cycling. Our research suggests that temporal variation in the propagation of ecological influence between adjacent systems generates phases when ecosystems are alternatively characterized as endogenously and exogenously controlled.

Enhancing the Engagement of U.S. Private Foundations with Conservation Science - ERIKA ZAVALETA; DANIEL C. MILLER; NICK SALAFSKY; ERICA FLEISHMAN; MICHAEL WEBSTER; BARRY GOLD; DAVID HULSE; MARY ROWEN; GARY TABOR; JACK VANDERRYN (Conservation Biology, 2008)
Funding for conservation is limited, and its investment for maximum conservation gain can likely be enhanced through the application of relevant science. Many donor institutions support and use science to pursue conservation goals, but their activities remain relatively unfamiliar to the conservation‐science community. We examined the priorities and practices of U.S.‐based private foundations that support biodiversity conservation. We surveyed 50 donor members of the Consultative Group on Biological Diversity (CGBD) to address three questions: (1) What support do CGBD members provide for conservation science? (2) How do CGBD members use conservation science in their grant making and strategic thinking? (3) How do CGBD members obtain information about conservation science? The 38 donor institutions that responded to the survey made $340 million in grants for conservation in 2005, including $62 million for conservation science. Individual foundations varied substantially in the proportion of conservation funds allocated to science. Foundations also varied in the ways and degree to which they used conservation science to guide their grant making. Respondents found it “somewhat difficult” to stay informed about conservation science relevant to their work, reporting that they accessed conservation science information mainly through their grantees. Many funders reported concerns about the strategic utility of funding conservation science to achieve conservation gains. To increase investment by private foundations in conservation science, funders, researchers, and conservation practitioners need to jointly identify when and how new scientific knowledge will lower barriers to conservation gains. We envision an evolving relationship between funders and conservation scientists that emphasizes primary research and synthesis motivated by (1) applicability, (2) human‐ecosystem interactions, (3) active engagement among scientists and decision makers, and (4) broader communication of relevant scientific information.

Negative learning - Michael Oppenheimer; Brian C. O’Neill; Mort Webster (Climatic Change, 2008)

An empirical evaluation of the nutrient‐color paradigm for lakes - Katherine E. Webster; Patricia A. Soranno; Kendra Spence Cheruvelil; Mary T. Bremigan; John A. Downing; Peter D. Vaux; Timothy R. Asplund; Linda C. Bacon; Jody Connor (Limnology and Oceanography, 2008)
We analyzed a diverse set of 1,646 north‐temperate lakes to evaluate the nutrient‐color paradigm that integrates total phosphorus (TP) and colored dissolved organic carbon to define lake trophic status. Our objectives were to quantify the combined influence of TP and color (Col) on lake trophic status, to determine if TP and Col had similar relationships with hydrogeomorphic (HGM) variables, and to examine how TP and Col affected the balance of heterotrophic and autotrophic processes. For the latter we examined the Col to chlorophyll a ratio (Col : Chl a), an index of allochthonous contributions of carbon to pelagic consumers, and deviations of lake p CO 2 from atmospheric, an index of net heterotrophy. Both Col and TP had strong effects on Chl a (positive) and Secchi transparency (negative), suggesting that ignoring Col would lead to misinterpretation of these widely used trophic status indicators. Lakes with high TP and Col tended to be shallower with large catchment to lake area ratios. Negative correlations with water retention time (WRT) were stronger for Col than for TP. Both TP and Col were related to forest and wetland land cover, although the direction of the relationships were opposite. Only 29% of the lakes had relatively high allochthony according to their Col : Chl a ratios; these were predominately high color, oligotrophic or mesotrophic lakes with short WRT. Over 90% of a subset of 682 lakes were net heterotrophic, with p CO 2 exceeding atmospheric levels. The positive relationship between p CO 2 and Col : Chl a suggests that only in very heterotrophic systems was the transfer of allochthonous carbon to pelagic consumers appreciable. Our results provide strong empirical support for the nutrient‐color paradigm and highlight its importance both for management applications and for expanding our understanding of how lakes are influenced by terrestrial subsidies of carbon and nutrients.

Modelling adaptive management strategies for coping with the impacts of climate variability and change on riverine algal blooms - NEIL R. VINEY; BRYSON C. BATES; STEPHEN P. CHARLES; IAN T. WEBSTER; MYRIAM BORMANS (Global Change Biology, 2007)
The impact of climate change on hydrology and water resources is one of the most critical issues facing the world in the next few decades. In particular, there is a need to quantify the risks associated with maintaining the security of resource quantity and quality, and to assess the effectiveness of potential management strategies. In this paper, we assess the impacts of climate variability and change on one aspect of river health. A simple model of Anabaena algal bloom occurrence at a weir pool in the lower Murrumbidgee River, Australia, has been coupled to a catchment model that is used to simulate streamflow, irrigation demand and diversions, dam water storage and releases, and decision‐making by both irrigators and managers. Long‐term climate data are obtained from a statistical downscaling algorithm, which, when applied to global climate model predictions can provide climate data suitable for driving the coupled model under a variety of climatic scenarios. The coupled model is then used to assess the impact of climate variability and projected climate change on the frequency, duration and magnitude of Anabaena blooms. The impact of two management strategies for bloom control are also assessed and it is shown that even a single, quite simple, resource‐neutral, adaptive management strategy has the potential to substantially reduce the occurrence and impact of algal blooms and to more than compensate for the deleterious impacts of climate change. This result supports the notion that planning for the future can lead to positive outcomes in the present.

Molecular characterization and cell-specific expression of an ion transport peptide in the tobacco hornworm, Manduca sexta - Anna L. Drexler; Christina C. Harris; Myra G. dela Pena; Marilyn Asuncion-Uchi; Sook Chung; Simon Webster; Megumi Fuse (Cell and Tissue Research, 2007)

Biogeochemistry and biodiversity of methane cycling in subsurface marine sediments (Skagerrak, Denmark) - R. John Parkes; Barry A. Cragg; Natasha Banning; Fiona Brock; Gordon Webster; John C. Fry; Ed Hornibrook; Richard D. Pancost; Sam Kelly; Nina Knab; Bo B. Jørgensen; Joachim Rinna; et al. (Environmental Microbiology, 2007)
Summary This biogeochemical, molecular genetic and lipid biomarker study of sediments (∼4 m cores) from the Skagerrak (Denmark) investigated methane cycling in a sediment with a clear sulfate‐methane‐transition zone (SMTZ) and where CH 4 supply was by diffusion, rather than by advection, as in more commonly studied seep sites. Sulfate reduction removed sulfate by 0.7 m and CH 4 accumulated below. 14 C‐radiotracer measurements demonstrated active H 2 /CO 2 and acetate methanogenesis and anaerobic oxidation of CH 4 (AOM). Maximum AOM rates occurred near the SMTZ (∼3 nmol cm −3 day −1 at 0.75 m) but also continued deeper, overall, at much lower rates. Maximum rates of H 2 /CO 2 and acetate methanogenesis occurred below the SMTZ but H 2 /CO 2 methanogenesis rates were × 10 those of acetate methanogenesis, and this was consistent with initial values of 13 C‐depleted CH 4 (δ 13 C c. −80‰). Areal AOM and methanogenic rates were similar (∼1.7 mmol m −2 day −1 ), hence, CH 4 flux is finely balanced. A 16S rRNA gene library from 1.39 m combined with methanogen (T‐RFLP), bacterial (16S rRNA DGGE) and lipid biomarker depth profiles showed the presence of populations similar to some seep sites: ANME‐2a (dominant), ANME‐3, Methanomicrobiales , Methanosaeta Archaea , with abundance changes with depth corresponding to changes in activities and sulfate‐reducing bacteria (SRB). Below the SMTZ to ∼1.7 m CH 4 became progressively more 13 C depleted (δ 13 C −82‰) indicating a zone of CH 4 recycling which was consistent with the presence of 13 C‐depleted archaeol (δ 13 C −55‰). Pore water acetate concentrations decreased in this zone (to ∼5 μM), suggesting that H 2 , not acetate, was an important CH 4 cycling intermediate. The potential biomarkers for AOM‐associated SRB, non‐isoprenoidal ether lipids, increased below the SMTZ but this distribution reflected 16S rRNA gene sequences for JS1 and OP8 bacteria rather than those of SRB. At this site peak rates of methane production and consumption are spatially separated and seem to be conducted by different archaeal groups. Also AOM is predominantly coupled to sulfate reduction, unlike recent reports from some seep and gassy sediment sites.

Environmental predictors of global parrot (Aves: Psittaciformes) species richness and phylogenetic diversity - Richard G. Davies; C. David L. Orme; Andrea J. Webster; Kate E. Jones; Tim M. Blackburn; Kevin J. Gaston (Global Ecology and Biogeography, 2007)
Aim Spatial patterns of phylogenetic diversity (PD) aid our ability to discern diversification rate mechanisms underlying hypotheses for the large‐scale distribution of biodiversity. We develop a predictive framework for the way in which spatial patterns of PD vary with those of species richness, depending on the balance between speciation and extinction rates. Within this framework, diversification processes thought to underlie the productive energy, ambient energy, topographic variability and habitat variety hypotheses predict that gradients of increase in species richness will be associated with: (1) decreasing extinction rates where driven by productive energy, hence increasing relative PD (i.e. PD controlling for species richness, or PD rel ); (2) a similar positive relationship between ambient energy and PD rel ; (3) increasing speciation rates where driven by topographic variability, hence decreasing PD rel ; and (4) no consistent relationship between PD rel and habitat variety when driven by the latter. We test these predictions using distributional data on parrots. Location Neotropical, Afrotropical, Indo‐Malayan and Australasian realms. Methods Spatial models were used to test the predictions. Results Globally, a positive association between productive energy and PD rel confirms prediction (1). However, within realms, hump‐shaped relationships suggest the importance of decreasing extinction rates up to a threshold level of productive energy, and the increasing importance of speciation rates thereafter. Ambient energy is positively associated with PD rel in Australasia, Indo‐Malaya, and globally, supporting prediction (2). However, this is driven by the coincidence of highest PD rel in areas of high ambient energy and intermediate productive energy (i.e. in seasonal tropical environments), which may be characterized by relatively low speciation and extinction rates. In the Neotropics, increasing topographic variability is associated with decreasing PD rel and increasing species richness, suggesting an increasing gradient of speciation, supporting prediction (3). Elsewhere, the signal of this mechanism may be obscured by collinearities with energy gradients. The lack of an overall relationship between habitat diversity and PD rel confirms prediction (4). Main conclusions Spatial patterns of PD rel in relation to environmental gradients may be sensitive to collinearities among those gradients. Nevertheless, patterns emerge which have implications for the relative importance of speciation and extinction processes in generating latitudinal diversity gradients.

Phytophthora inundata from native vegetation in Western Australia - M. J. C. Stukely; J. L. Webster; J. A. Ciampini; E. Brown; W. A. Dunstan; G. E. St J. Hardy; G. J. Woodman; E. M. Davison; F. C. S. Tay (Australasian Plant Pathology, 2007)

Transgenic mice expressing PAX3-FKHR have multiple defects in muscle development, including ectopic skeletal myogenesis in the developing neural tube - Friedrich Graf Finckenstein; Elai Davicioni; Kent G. Osborn; Webster K. Cavenee; Karen C. Arden; Michael J. Anderson (Transgenic Research, 2006)

Systematic review and meta-analysis of antifungal agents for preventing fungal infections in liver transplant recipients - E. G. Playford; A. C. Webster; T. C. Sorrell; J. C. Craig (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

A comparison of stable‐isotope probing of DNA and phospholipid fatty acids to study prokaryotic functional diversity in sulfate‐reducing marine sediment enrichment slurries - Gordon Webster; Lynsey C. Watt; Joachim Rinna; John C. Fry; Richard P. Evershed; R. John Parkes; Andrew J. Weightman (Environmental Microbiology, 2006)
Summary Marine sediment slurries enriched for anaerobic, sulfate‐reducing prokaryotic communities utilizing glucose and acetate were used to provide the first comparison between stable‐isotope probing (SIP) of phospholipid fatty acids (PLFA) and DNA (16S rRNA and dsrA genes) biomarkers. Different 13 C‐labelled substrates (glucose, acetate and pyruvate) at low concentrations (100 µM) were used over a 7‐day incubation to follow and identify carbon flow into different members of the community. Limited changes in total PLFA and bacterial 16S rRNA gene DGGE profiles over 7 days suggested the presence of a stable bacterial community. A broad range of PLFA were rapidly labelled (within 12 h) in the 13 C‐glucose slurry but this changed with time, suggesting the presence of an active glucose‐utilizing population and later development of another population able to utilize glucose metabolites. The identity of the major glucose‐utilizers was unclear as 13 C‐enriched PLFA were common (16:0, 16:1, 18:1ω7, highest incorporation) and there was little difference between 12 C‐ and 13 C‐DNA 16S rRNA gene denaturing gradient gel electrophoresis (DGGE) profiles. Seemingly glucose, a readily utilizable substrate, resulted in widespread incorporation consistent with the higher extent of 13 C‐incorporation (∼10 times) into PLFA compared with 13 C‐acetate or 13 C‐pyruvate. 13 C‐PLFA in the 13 C‐acetate and 13 C‐pyruvate slurries were similar to each other and to those that developed in the 13 C‐glucose slurry after 4 days. These were more diagnostic, with branched odd‐chain fatty acids ( i 15:0, a 15:0 and 15:1ω6) possibly indicating the presence of Desulfococcus or Desulfosarcina sulfate‐reducing bacteria (SRB) and sequences related to these SRB were in the 13 C‐acetate‐DNA dsrA gene library. The 13 C‐acetate‐DNA 16S rRNA gene library also contained sequences closely related to SRB, but these were the acetate‐utilizing Desulfobacter sp., as well as a broad range of uncultured Bacteria. In contrast, analysis of DGGE bands from 13 C‐DNA demonstrated that the candidate division JS1 and Firmicutes were actively assimilating 13 C‐acetate. Denaturing gradient gel electrophoresis also confirmed the presence of JS1 in the 13 C‐DNA from the 13 C‐glucose slurry. These results demonstrate that JS1, originally found in deep subsurface sediments, is more widely distributed in marine sediments and provides the first indication of its metabolism; incorporation of acetate and glucose (or glucose metabolites) under anaerobic, sulfate‐reducing conditions. Here we demonstrate that PLFA‐ and DNA‐SIP can be used together in a sedimentary system, with low concentrations of 13 C‐substrate and overlapping incubation times (up to 7 days) to provide complementary, although not identical, information on carbon flow and the identity of active members of an anaerobic prokaryotic community.

Pulmonary Vascular Resistance and Impedance in Isolated Mouse Lungs: Effects of Pulmonary Emboli - Holly A. Tuchscherer; Eidan B. Webster; Naomi C. Chesler (Annals of Biomedical Engineering, 2006)

The potential role of lamotrigine in schizophrenia - Charles H. Large; Elizabeth L. Webster; Donald C. Goff (Psychopharmacology, 2005)

Enhancement of 2,4-dinitrotoluene biodegradation by Burkholderia sp. in sand bioreactors using bacterial hemoglobin technology - Juho So; Dale A. Webster; Benjamin C. Stark; Krishna R. Pagilla (Biodegradation, 2004)

Diversity of prokaryotes and methanogenesis in deep subsurface sediments from the Nankai Trough, Ocean Drilling Program Leg 190 - Carole J. Newberry; Gordon Webster; Barry A. Cragg; R. John Parkes; Andrew J. Weightman; John C. Fry (Environmental Microbiology, 2004)
Summary Diversity of Bacteria and Archaea was studied in deep marine sediments by PCR amplification and sequence analysis of 16S rRNA and methyl co‐enzyme M reductase ( mcrA ) genes. Samples analysed were from Ocean Drilling Program (ODP) Leg 190 deep subsurface sediments at three sites spanning the Nankai Trough in the Pacific Ocean off Shikoku Island, Japan. DNA was amplified, from three depths at site 1173 (4.15, 98.29 and 193.29 mbsf; metres below the sea floor), and phylogenetic analysis of clone libraries showed a wide variety of uncultured Bacteria and Archaea . Sequences of Bacteria were dominated by an uncultured and deeply branching ‘deep sediment group’ (53% of sequences). Archaeal 16S rRNA gene sequences were mainly within the uncultured clades of the Crenarchaeota . There was good agreement between sequences obtained independently by cloning and by denaturing gradient gel electrophoresis. These sequences were similar to others retrieved from marine sediment and other anoxic habitats, and so probably represent important indigenous bacteria. The mcrA gene analysis suggested limited methanogen diversity with only three gene clusters identified within the Methanosarcinales and Methanobacteriales . The cultivated members of the Methanobacteriales and some of the Methanosarcinales can use CO 2 and H 2 for methanogenesis. These substrates also gave the highest rates in 14 C‐radiotracer estimates of methanogenic activity, with rates comparable to those from other deep marine sediments. Thus, this research demonstrates the importance of the ‘deep sediment group’ of uncultured Bacteria and links limited diversity of methanogens to the dominance of CO 2 /H 2 based methanogenesis in deep sub‐seafloor sediments.

Phylogeography of Biomphalaria glabrata and B. pfeifferi , important intermediate hosts of Schistosoma mansoni in the New and Old World tropics - R. J. Dejong; J. A. T. Morgan; W. D. Wilson; M. H. Al‐Jaser; C. C. Appleton; G. Coulibaly; P. S. D’Andrea; M. J. Doenhoff; W. Haas; M. A. Idris; L. A. Magalhães; H. Moné; et al. (Molecular Ecology, 2003)
The historical phylogeography of the two most important intermediate host species of the human blood fluke Schistosoma mansoni , B. glabrata in the New World, and B. pfeifferi in the Old World, was investigated using partial 16S and ND1 sequences from the mitochondrial genome. Nuclear sequences of an actin intron and internal transcribed spacer (ITS)‐1 were also obtained, but they were uninformative for the relationships among populations. Phylogenetic analyses based on mtDNA revealed six well‐differentiated clades within B. glabrata : the Greater Antilles, Venezuela and the Lesser Antilles, and four geographically overlapping Brazilian clades. Application of a Biomphalaria ‐specific mutation rate gives an estimate of the early Pleistocene for their divergence. The Brazilian clades were inferred to be the result of fragmentation, due possibly to climate oscillations, with subsequent range expansion producing the overlapping ranges. Within the Venezuela and Lesser Antilles clade, lineages from each of these areas were estimated to have separated approximately 740 000 years ago. Compared to B. glabrata , mitochondrial sequences of B. pfeifferi are about 4× lower in diversity, reflecting a much younger age for the species, with the most recent common ancestor of all haplotypes estimated to have existed 880 000 years ago. The oldest B . pfeifferi haplotypes occurred in southern Africa, suggesting it may have been a refugium during dry periods. A recent range expansion was inferred for eastern Africa less than 100 000 years ago. Several putative species and subspecies, B. arabica, B. gaudi, B. rhodesiensis and B. stanleyi , are shown to be undifferentiated from other B. pfeifferi populations.

Pre-eruptive geochemistry of the ignimbrite-forming magmas of the Campanian Volcanic Zone, Southern Italy, determined from silicate melt inclusions - J. D. Webster; F. Raia; C. Tappen; B. De Vivo (Mineralogy and Petrology, 2003)

Biodegradation of 2-Chlorobenzoate by Recombinant Burkholderia Cepacia Expressing Vitreoscilla Hemoglobin Under Variable Levels of Oxygen Availability - Meltem Urgun-Demirtas; Krishna R. Pagilla; Benjamin C. Stark; Dale Webster (Biodegradation, 2003)

Chronic Bronchitis in Immunocompromised Patients: Association with a Novel Mycoplasma Species - D. Webster; H. Windsor; C. Ling; D. Windsor; D. Pitcher (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Evidence for stable transformation of Pseudomonas aeruginosa with a pUC-based plasmid - Benjamin C. Stark; Yongsoon Kim; Dale A. Webster (Biotechnology Letters, 2003)

Identification and characterization of members of the FKHR (FOX O) subclass of winged-helix transcription factors in the mouse - William H. Biggs III; Webster K. Cavenee Karen C. (Mammalian Genome, 2001)

Predicting Human Oral Bioavailability of a Compound: Development of a Novel Quantitative Structure-Bioavailability Relationship - C. Webster Andrews; Lee Bennett; Lawrence X. Yu (Pharmaceutical Research, 2000)

Boron in the Bolivian tin belt - B. Lehmann; A. Dietrich; J. Heinhorst; N. Métrich; M. Mosbah; C. Palacios; H. -J. Schneider; A. Wallianos; J. Webster; L. Winkelmann (Mineralium Deposita, 2000)

Soluble organic nitrogen in agricultural soils - D. V. Murphy; A. J. Macdonald; E. A. Stockdale; K. W. T. Goulding; S. Fortune; J. L. Gaunt; P. R. Poulton; J. A. Wakefield; C. P. Webster; W. S. Wilmer (Biology and Fertility of Soils, 2000)

Molecular and Antibiogram Relationships of Acinetobacter Isolates from Two Contrasting Hospitals in the United Kingdom and South Africa - C. A. Webster; K. J. Towner; G. L. Saunders; H. H. Crewe-Brown; H. Humphreys (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

A/T-rich sequences act as quantitative enhancers of gene expression in transgenic tobacco and potato plants - Jagdeep S. Sandhu; Carl I. Webster; John C. Gray (Plant Molecular Biology, 1998)

Surveillance of an Adult Intensive Care Unit for Long-Term Persistence of a Multi-Resistant Strain of Acinetobacter baumannii - C. A. Webster; M. Crowe; H. Humphreys; K. J. Towner (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

Characterisation and promoter analysis of the Arabidopsis gene encoding high-mobility-group protein HMG-I/Y - Rajeev Gupta; Carl I. Webster; John C. Gray (Plant Molecular Biology, 1998)

Decreased gap-junctional communication associated with segregation of the neuronal phenotype in the RT4 cell-line family - L. M. Donahue; Daniel R. Webster; Ivvanee Martinez; David C. Spray (Cell and Tissue Research, 1998)

Dual-chamber cardiac pacemaker tester - C. W. Galuschky; J. G. Webster (Medical & Biological Engineering & Computing, 1998)

Surveillance of an adult intensive care unit for long-term persistence of a multi-resistant strain ofAcinetobacter baumannii - C. A. Webster; M. Crowe; H. Humphreys; K. J. Towner (European Journal of Clinical Microbiology & Infectious Diseases, 1998)

The single-copy gene encoding high-mobility-group protein HMG-I/Y from pea contains a single intron and is expressed in all organs - Rajeev Gupta; Carl I Webster; John C Gray (Plant Molecular Biology, 1997)

Interactions of rhizobia with rice and wheat - G. Webster; C. Gough; J. Vasse; C.A. Batchelor; K.J. O'Callaghan; S.L. Kothari; M.R. Davey; J. Dénarié; E.C. Cocking (Plant and Soil, 1997)

Chromosomal location and expression of the single-copy gene encoding high-mobility-group protein HMG-I/Y in Arabidopsis thaliana - Rajeev Gupta; Carl I. Webster; Amanda R. Walker; John C. Gray (Plant Molecular Biology, 1997)

Apiculture and forestry (bees and trees) - D. B. Hill; T. C. Webster (Agroforestry Systems, 1995)

Relation between drug resistance and antigenicity among norakin-resistant mutants of influenza A (fowl plague) virus - A. I. Klimov; S. G. Markushin; S. Prsch; V. P. Ginzburg; H. Heider; A. M. Heider; C. Schreder; R. G. Webster (Archives of Virology, 1992)

Electron microscopic evidence for the association of M 2 protein with the influenza virion - D. C. Jackson; Xi-Lin Tang; K. Gopal Murti; R. G. Webster; G. W. Tregear; W. J. Bean (Archives of Virology, 1991)

Influenza viral infection of swine in the United States 1988?1989 - T. M. Chambers; Virginia S. Hinshaw; Y. Kawaoka; B. C. Easterday; R. G. Webster (Archives of Virology, 1991)

Identification of b, c, and d cytochromes in the membrane of Vitreoscilla - C. D. Georgiou; D. A. Webster (Archives of Microbiology, 1987)

Persistence of Q strain of H2N2 influenza virus in avian species: Antigenic, biological and genetic analysis of avian and human H2N2 viruses - K. Nerome; Y. Yoshioka; C. A. Torres; A. Oya; P. Bachmann; K. Ottis; R. G. Webster (Archives of Virology, 1984)

Antigenic analysis of influenza A virus surface antigens: Considerations for the nomenclature of influenza virus - G. C. Schild; R. W. Newman; R. G. Webster; Diane Major; Virginia S. Hinshaw (Archives of Virology, 1980)

Isolation and serological characterization of influenza A viruses from birds that were dead on arrival at Tokyo airport - K. Nerome; M. Nakayama; M. Ishida; H. Fukumi; W. K. Butterfield; R. G. Webster; C. H. Campbell (Archives of Virology, 1978)